Thermal Tolerance of Geographical Populations and Their Hybrids in the Ivory Shell Babylonia areolata - Jingqiang Fu; Linwei Nie; Zhenzhen Cai; Weiguang Zou; Yuan Liang; Wengang Lü; Minghui Shen; Xuan Luo; Weiwei You; Tuanyu Guo; Caihuan Ke (Fishes, 2026)
Global warming and summer heatwaves increasingly threaten the survival of cultured Babylonia areolata, but the heat tolerance of different geographical populations and the potential for genetic improvement by hybridization remain poorly understood. In this study, four geographical populations (Thailand, TL; Wanning, WN; Zhao’an, ZA; Changle, CL) and four hybrid combinations (TH, HT, TF, and FT) were compared for mortality rate, median lethal temperature (LT50), and critical thermal maximum (CTMax) under controlled thermal stress. The results showed that the low-latitude TL population exhibited significantly higher LT50 (36.49 ± 0.05 °C) and CTMax (35.77 ± 0.52 °C) than the high-latitude CL and ZA populations (LT50: 35.90 ± 0.05–36.02 ± 0.04 °C; CTMax: 35.12 ± 0.77–35.26 ± 0.53 °C). All four hybrids had improved heat tolerance compared with their low parents, with TH and HT showing the strongest mid-parent heterosis (e.g., 73.68–78.94% for survival at 36.5 °C). However, none significantly exceeded the high-parent performance (TL), indicating only mid-parent heterosis. These findings reveal significant genetic variation in heat tolerance among geographical populations of B. areolata and confirm that cross-breeding can effectively enhance heat tolerance, though it does not produce transgressive superiority. This study provides key genetic resources and a theoretical basis for breeding heat-tolerant strains of B. areolata.